2007
DOI: 10.1007/s10162-007-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Distribution of Medial Olivocochlear Acoustic Reflex Strengths Across Normal-Hearing Individuals via Otoacoustic Emissions

Abstract: A clinical test for the strength of the medial olivocochlear reflex (MOCR) might be valuable as a predictor of individuals at risk for acoustic trauma or for explaining why some people have trouble understanding speech in noise. A first step in developing a clinical test for MOCR strength is to determine the range and variation of MOCR strength in a research setting. A measure of MOCR strength near 1 kHz was made across a normalhearing population (N=25) by monitoring stimulusfrequency otoacoustic emissions (SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
74
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 28 publications
15
74
1
Order By: Relevance
“…This pattern is consistent with the suppression acting in the tonotopic region of the probe tone, i.e., that the place of generation of the SFOAE residual did not vary as the suppressor frequency varied (Keefe et al 2008). In addition, in three subjects, Backus and Guinan (2007) found that as "suppressor" tones were increased in frequency, the residual decreased to the noise floor at about 1 octave above the probe frequency. In contrast to these patterns, in chinchillas and cats, large residuals (often larger than the residual produced by "suppressors" near the probe frequency) were found with suppressors many octaves above the probe frequency and the phase of these residuals varied dramatically with "suppressor" frequency.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This pattern is consistent with the suppression acting in the tonotopic region of the probe tone, i.e., that the place of generation of the SFOAE residual did not vary as the suppressor frequency varied (Keefe et al 2008). In addition, in three subjects, Backus and Guinan (2007) found that as "suppressor" tones were increased in frequency, the residual decreased to the noise floor at about 1 octave above the probe frequency. In contrast to these patterns, in chinchillas and cats, large residuals (often larger than the residual produced by "suppressors" near the probe frequency) were found with suppressors many octaves above the probe frequency and the phase of these residuals varied dramatically with "suppressor" frequency.…”
Section: Discussionmentioning
confidence: 89%
“…To measure the SFOAE by suppression, we presented a 40-dB SPL probe tone with and without a suppressor (a 60-dB SPL tone, 110 Hz below the probe frequency presented for 500 ms every second) and calculated the SFOAE as the vector difference between the probefrequency ear-canal sound pressures with and without the suppressor. Although Backus and Guinan (2007) found that these parameter values produce only 80-100% suppression, this did not affect the shape of the MOC-effect curves because, for a given ear, all points were normalized by the same SFOAE magnitude. For both suppressor tones and MOC elicitors, 5-ms rise/ fall cosine ramps were used to minimize spectral splatter.…”
Section: Acoustic Stimulimentioning
confidence: 93%
“…This is in agreement with previous work. In their study examining individual MOC shifts using SFOAEs, Backus and Guinan (2007) found that in a given individual, MOC shifts were sometimes present at a given frequency but absent at other nearby frequencies. In the current study, TEOAEs were analyzed in 11 1/3-octave frequency bands.…”
Section: Mocr Frequency Effectsmentioning
confidence: 99%
“…Detection of statistically significant MOC shifts in individuals using a bootstrapping technique was described by Backus and Guinan (2007). The authors measured MOC shifts using stimulus frequency (SF) OAEs, which are sensitive probes of the MOCR; however, measurement can be time consuming because frequencies must be tested individually.…”
mentioning
confidence: 99%
“…Depending on the duration of the masker, the activation of the MOCR may complicate interpretation of TMCs if forward-masked thresholds measured at shorter masker-probe intervals reflect a different cochlear process than thresholds measured at longer intervals. Relevant to the current experiment, the MOCR may contribute to individual differences to the extent that characteristics of the MOCR vary among individuals with similar hearing sensitivity (Backus and Guinan 2007;Lilaonitkul and Guinan 2009), as in the notion of "tough" and "tender" ears related to noise susceptibility (Maison and Liberman 2000). The MOCR was not assessed in the current experiment; additional research is necessary to determine the extent to which the MOCR affects compression estimates inferred from TMCs and contributes to individual differences in these measures (Wojtczak and Oxenham 2010).…”
Section: Linear-reference Tmcs Using Higher Frequency Signalsmentioning
confidence: 99%